Cost‐effectiveness analysis of primary human papillomavirus testing in cervical cancer screening: Results from the HPV FOCAL Trial. (2nd April 2021) - Cromwell, Ian; Smith, Laurie W.; van der Hoek, Kim; Hedden, Lindsay; Coldman, Andrew J.; Cook, Darrel; Franco, Eduardo L.; Krajden, Mel; Martin, Ruth; Lee, Marette H.; Stuart, Gavin; van Niekerk, Dirk; et al.
Abstract: The Human Papillomavirus FOr CervicAL cancer (HPV FOCAL) trial is a large randomized controlled trial comparing the efficacy of primary HPV testing to cytology among women in the population‐based Cervix Screening Program in British Columbia, Canada. We conducted a cost‐effectiveness analysis based on the HPV FOCAL trial to estimate the incremental cost per detected high‐grade cervical intraepithelial neoplasia of grade 2 or worse lesions (CIN2+). A total of 19, 009 women aged 25 to 65 were randomized to one of two study groups. Women in the intervention group received primary HPV testing with reflex liquid‐based cytology (LBC) upon a positive finding with a screening interval of 48 months. Women in the control group received primary LBC testing, and those negative returned at 24 months for LBC and again at 48 months for exit screening. Both groups received HPV and LBC co‐testing at the 48‐month exit. Incremental costs during the course of the trial were comparable between the intervention and control groups. The intervention group had lower overall costs and detected a larger number of CIN2+ lesions, resulting in a lower mean cost per CIN2+ detected (7551) than the control group (8325), a difference of ‐773 [all costs in 2018 USD]. Cost per detected lesion was sensitive to the costs of sample collection, HPV testing, and LBC testing. The HPV FOCAL Trial results suggest that primary HPV testing every 4 years produces similar outcomes to LBC‐based testing every 2 years for cervical cancer screening at a lower cost. Abstract : The Human Papillomavirus FOr CervicAL cancer (HPV FOCAL) trial is a large randomized controlled trial comparing primary HPV testing to liquid‐based cytology for cervical cancer screening. We conducted a cost‐effectiveness analysis alongside the HPV FOCAL trial. Results showed the intervention group yielded a higher rate of detected cervical intraepithelial neoplasia of grade 2 or worse lesions (CIN2+) at a lower mean cost per CIN2+ detected (7551) than the control group (8325), a difference of −773. Findings suggest that primary HPV testing is cost‐effective compared to liquid‐based cytology.